Regression in thin melanoma is associated with nodal recurrence after a negative sentinel node biopsy. (27th September 2016) - Rubinstein, Jill C.; Han, Gang; Jackson, Laura; Bulloch, Kaleigh; Ariyan, Stephan; Narayan, Deepak; Rothberg, Bonnie G.; Han, Dale
Abstract: Prognostic markers for nodal metastasis in thin melanoma patients are debated. We present a single institution study looking at factors predictive of nodal disease in thin melanoma patients. Retrospective review from 1997 to 2012 identified 252 patients with thin melanoma (≤1 mm) who underwent a sentinel lymph node biopsy (SLNB). Node‐positive patients included positive SLNB patients and negative SLNB patients who developed a nodal recurrence (false‐negative SLNB). Clinicopathologic characteristics were correlated with nodal status and outcome. Median follow‐up was 45.5 months. Twelve of 252 patients (4.8%) were node‐positive including six positive SLNB (2.4%) and six false‐negative SLNB (2.4%) patients. No clinicopathologic factors were significantly correlated with nodal disease. For the six false‐negative SLNB patients, median time to nodal recurrence was 37.5 months. Regression was seen in only 16% of cases, but the rate increased to 60% for false‐negative SLNB cases. Both age (odds ratio [OR]: 1.09, 95% CI: 1.01–1.17; P  = 0.02) and regression (OR: 8.33, 95% CI: 1.34–52.63; P  = 0.02) were significantly associated with nodal recurrence after a negative SLNB on univariable analysis. Nodal disease in thin melanoma patients was seen in 4.8% of cases. Although regression was not correlated with nodal metastasis, it was correlated with a false‐negative SLNB. Patients with thin melanoma and regression may need more intensive surveillance after a negative SLNB. Further study is needed to determine if the same immune mechanisms that result in regression in primary tumors also lead to regression in lymph nodes, which may decrease detection of melanoma nodal metastases. Abstract : Prognostic markers for nodal metastasis in thin melanoma patients are debated. In this single institution study looking at factors predictive of nodal disease in thin melanoma patients, regression was not correlated with nodal metastasis, but it was correlated with a false‐negative sentinel lymph node biopsy. Patients with thin melanoma and regression may need more intensive surveillance after a negative sentinel lymph node biopsy (SLNB).